Síndrome da dor femoropatelar análise eletromiográfica, isocinética, ressonância magnética, dor e fadiga - Souza, Alessandra de Castro (Universidade Federal de São Carlos, 2005)
The purpose of this work was to analyze the electrical activity (EMG) of the vastus medialis obliquus (VMO) and vastus lateralis longus (VLL) and vastus lateralis obliquus (VLO) in association with the evaluation of the maximum isometric torque (MIT) of the quadriceps muscle, during the maximum voluntary isometric contraction (MVIC) of knee extension in open kinetic chain (OKC) at 20o, 30o, 50o and 60o of knee flexion, also, pain and fatigue and the aspects in relation to patellae positioning: the sulcus angle (SA), the congruence angle (CA), patellar tilt angle (PTA) and lateral patellar displacement (LDP). Twenty four female subjects were evaluated (12 with patellofemoral pain syndrome PFPS and 12 clinically normal controls). For the EMG analysis simple surface differential active electrodes and a Signal Conditioner Module (MCS 1000-v2) were used. The electromyographic signal was quantified by the Root Mean Square (RMS), in µV, and normalized by the MVIC of 90o of knee extension. The subjects made 5 MVIC of knee extension, at 30o of flexion for the EMG and MMIT analysis and the NMRI with the quadriceps muscle relaxed were obtained at the same angles. The following statistic tests were used: ANOVA Analysis of Variance with Repeated Measurements for the EMG and MMIT analysis; the Mann-Whitney U test for the NMRI; and the One Way Analysis of Variance for the evaluation of intensity and discomfort from pain and fatigue (p ≤ 0.05). The results showed a higher electrical activity of the VLL muscle in relation to the VMO in the group with FPPS. The control group, the VMO and VLL did not present a significant difference in all studied angles. In both groups, VMO and VLL showed a higher electrical activity in comparison with VLO, in all angles. The MMIT values of the quadriceps did not differ among groups, however it did differ between angles. The highest MMIT value was 60o. The NMRI analysis revealed that the FPPS group presented higher values of SA and lower values of CA in relation to the Control group. The results showed an increase in pain and fatigue of the subjects with PFPS after the MVIC and in comparison with the Control group. The data of this study, on the experimental conditions, suggest that: a higher electrical activity of the VLL in addition with the increase in SA and decrease in CA in the subjects with PFPS can be factors favoring such individuals patellar instability. Pain and fatigue were greater in subjects with PFPS. The results showed that the EMG and the NMRI were instruments capable of differentiating the groups that were studied.
Keywords: Eletromiografia; Femoropatelar; Dor; Vasto medial oblíquio; Ressonância magnética; Patellofemoral Pain Syndrome; Electromyography; Magnetic Resonance; Dynamometry; Vastus Medialis Obliquus; Vastus Lateralis Obliquus; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL